Biologic Therapy in Immune Mediated Inflammatory Disease: Basic Science and Clinical Concepts - Molinelli, E.; Campanati, A.; Ganzetti, G.; Offidani, A. (Current Drug Safety, 2016)
During the last decades, the advent of biological therapies has revolutionized the management of several immune-mediated inflammatory disorders, as inflammatory bowel diseases, autoimmune arthritis and psoriasis, which significantly impact both quality of life and health care economics. Biological therapies currently available can be divided into two main categories: the tumor necrosis factor-α antagonists (infliximab, adalimumab, etanercept, golimumab, certolizumab pegol) and interleukin 12/23 monoclonal antibodies (ustekinumab). Biologics, reducing TNFα bioavailability or inhibiting proximal regulators of inflammatory cascade, represent an established therapeutic strategy of inflammatory autoimmune diseases, with remarkable efficacy and a safety profile that is extensively examined and monitored. The biology and the immunological effects of TNFα, IL-12, IL-23 and related signalling pathways are accurately summarized. The dosing regimens, methods of administration, pharmacodynamics profiles, and side effects of the currently licensed TNFα antagonists and IL12/IL23 inhibitor are discussed in detail.
Keywords: Adverse events